Top Stem Careers in Engineering - Gina Hagler
Engineers blend logic and precision with imagination, and science and math principles with vision and foresight, to create solutions for some of society's most pressing problems. From information technology to medicine, public transportation to space travel, engineers work to make innovation a reality. This inspiring book explores a variety of branches of engineering, discussing the opportunities available, typical work environments, and educational credentials needed to enter each field. Readers learn ways to enhance their background by participating in engineering organizations, science clubs, internships, research projects, and community service. Amazing full-color photos of real-life projects illustrate engineering processes in action.